Influence of Debt Policy and Share Prices on Firm Performance - Oktaviani, Marista; Sari, Tyasha Ayu Melynda; Setiawan, Adhar Putra (Journal of Culture Accounting and Auditing, 2023)
The purpose of this research is to determine debt policy and share prices on company performance. The research period is 2017-2020 with the research object being banking companies. The research method used. The type of research used is quantitative research with purposeful sampling techniques. This research data analysis technique uses multiple linear regression. The research results of the Current Ratio are negative and not significant for Firm Performance and the Debt Equity Ratio is negative and significant for Firm Performance. The use of debt means supervision of management is not only carried out by shareholders, but also by creditors. The greater the debt component used by a bank in carrying out its operational activities, the worse it will have an impact on the bank's profitability. The higher the DER a bank has, the lower the level of profit (ROA). Share Prices Are Positive and Significant on Firm Performance in Banking Companies. The share price also shows the value of a company and is an appropriate index for company effectiveness, so the higher the share price, the higher the company value.